2015
DOI: 10.3906/sag-1308-3
|View full text |Cite
|
Sign up to set email alerts
|

Mucocutaneous manifestations and the relationship to CD4 lymphocyte counts among Turkish HIV/AIDS patients in İstanbul, Turkey

Abstract: Background/aim: Dermatologic findings differ among countries but no sufficient data about Turkish HIV-infected patients exist in the literature. Therefore, our aim in this study was to document the dermatologic manifestations and their relationships with CD4 cell counts among HIV/AIDS patients visiting our clinic for the first time in İstanbul, Turkey. Materials and methods:A retrospective analysis of 306 HIV/AIDS patients (260 men, mean age: 38.3 years) was done in a tertiary hospital in İstanbul from January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
15
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 16 publications
5
15
1
1
Order By: Relevance
“…Some dermatological signs and symptoms suggest the diagnosis of HIV infection, such as shingles in young adults and disseminated prurigo, whereas others have diagnostic value, such as oral hairy leukoplakia, or prognostic value, such Kaposi's sarcoma, indicating an advanced stage of the disease . Different studies have been attempting to establish a correlation between CD 4 T cell counts and systemic changes . HIV‐positive patients may present a variety of dermatologic manifestations …”
mentioning
confidence: 99%
“…Some dermatological signs and symptoms suggest the diagnosis of HIV infection, such as shingles in young adults and disseminated prurigo, whereas others have diagnostic value, such as oral hairy leukoplakia, or prognostic value, such Kaposi's sarcoma, indicating an advanced stage of the disease . Different studies have been attempting to establish a correlation between CD 4 T cell counts and systemic changes . HIV‐positive patients may present a variety of dermatologic manifestations …”
mentioning
confidence: 99%
“…4,9 Unsafe sex was the highest risk factor of HIV transmission in this study. Aydin et al 5 reported the main risk of HIV transmission among Turkish HIV/AIDS patients in Istanbul was unsafe sex. In the mid 1990s, IVDU was the highest risk factor for HIV transmission in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…Mucocutaneous manifestations can be increased with the development of HIV and CD4 decline. 5 Mucocutaneous manifestations in HIV patients can be found as infection, noninfection and tumor. In developed countries, non-infection cases in HIV patients commonly encountered due to the differences in their skin pigmentation, climate, hygiene, genetic, environment, demographic and behavioral patterns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations